ANALISIS KUALITAS PELAYANAN DI UNIT PELAKSANAAN TEKNIS PEMELIHARAAN KESEHATAN MASYARAKAT SURAKARTA - Fania Anindita; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study aims to determine the quality of public services and restricted dimensions of Technical Implementation Unit Public Health Maintenance of Surakarta . This study uses five dimensions theory of Service Quality namely Tangible, Reliability, Responsiveness, Assurance and Empathy. This research method is a descriptive study with qualitative approach. The data collection is done by observation, interview and documentation. Data analysis of in this study uses three components consisting of data reduction, data presentation, and conclusion. The results of this study show that, quality of service rendered by the UPT PKMS to participants PKMS is not maximized, the views of the five dimensions of service quality, there are two dimensions that hamper the quality of service such as tangible dimension includingcomfort of waiting room and assurance dimension includingtime guarantee. The tangiable dimensions that hinder service quality includingcomfort of waiting room can be seen from the quality of the reception area that there is only a chair in the hallway of the road besides the absence of procurement tables and lack of air conditioning made the quality of services has not been maximized. Assurance dimensionincluding time guarantee given by UPT PKMS to the public is also not maximized, the views from the appropriate service process card five to seven working days, but in fact the process of card services in excess of the specified time.